Norms According to Age and Gender for the Spanish Version of the Inventory of Depression and Anxiety Symptoms (IDAS-II) - Sanchez-Garcia, Manuel; De la Rosa-Cáceres, Ana; Stasik-O'Brien, Sara; Mancheño-Barba, Juan José; Lozano, Óscar M.; Diaz-Batanero, Carmen (Frontiers in Psychology, 2021)
Inventory of Depression and Anxiety Symptoms-II constitutes a useful measurement tool with demonstrated psychometric properties that is contributing to the advancement of knowledge of emotional disorders within transdiagnostic models. To implement its use in clinical settings it is important that the scores can be interpreted in order to guide clinical decisions. This study aims to develops normative data for the Spanish version of the IDAS-II. An anonymous online survey was applied to 1072 subjects, recruited through a stratified random sampling procedure taking into account population gender, age and geographical region of Spain. Results show that women tend to score higher than men, particularly on the Dysphoria, General Depression, Appetite Gain and Lassitude scales. Largest effect sizes for differences in the scores according to age were found for Lassitude, Dysphoria and General Depression. Therefore, normative data according to gender and age group for each IDAS-II scale is provided. The norms provided in this work complement those already available, facilitating the decision-making of clinical professionals. Evidence of unidimensionality is provided for the 19 IDAS-II scales that allows researchers and clinicians to use specific IDAS-II scales independently.